Competing Emergencies: A Policy Analysis of the Opioid Epidemic during COVID-19. Issue 1 (2nd January 2021) - Pérez-Chiqués, Elizabeth; Strach, Patricia; Zuber, Katie
Abstract: The response to COVID-19 brought rapid policy change to substance-use services in the US and redefined its street-level bureaucrats (SLBs) as essential workers. What effect did policy changes have on SLB discretion and roles? This article examines policies prior to and after the onset of the pandemic and analyzes the implications for practice through interviews with managerial and executive staff in the substance-use field in New York State. In governments' attempt to balance the risk of competing emergencies, the effects of the simultaneous extension and contraction of different types of discretion on organizations and their frontline workers are shown. Note: In the interests of space, street-level theory and the pandemic context underpinning the articles for this Special Issue are discussed in detail in the Introduction to the Issue.